Genome-Wide Identification of 14-3-3 gene family reveals their diverse responses to abiotic stress by interacting with StABI5 in Potato (Solanum tuberosum L.) - Wang, Qianqian; Yan, Chongchong; Fu, Yuying; Wang, Yu; Jiang, Pengfei; Ding, Yinyuan; Liao, Huajun (Frontiers in Plant Science, 2023)
The 14-3-3 genes are widely present in plants and participate in a wide range of cellular and physiological processes. In the current study, twelve 14-3-3s were identified from potato genome. According to phylogenetic evolutionary analysis, potato 14-3-3s were divided into ε and non-ε groups. Conserved motif and gene structure analysis displayed distinct class-specific divergence between the ε group and non-ε group. Multiple sequences alignment and three-dimensional structure analysis of 14-3-3 proteins analysis indicated all the members contained nine conservative antiparallel α-helices. The majority of 14-3-3s had transcript accumulation in each detected potato tissue, implying their regulatory roles across all stages of potato growth and development. Numerous cis-acting elements related to plant hormones and abiotic stress response were identified in the promoter region of potato 14-3-3s, and the transcription levels of these genes fluctuated to different degrees under exogenous ABA, salt and drought stress, indicating that potato 14-3-3s may be involved in different hormone signaling pathways and abiotic stress responses. In addition, eight potato 14-3-3s were shown to interact with StABI5, which further demonstrated that potato 14-3-3s were involved in the ABA-dependent signaling pathway. These results provide useful information for further functional characterization of 14-3-3s in potato.